Framing Media dan Bias Gender dalam Fenomena Pelakor dan Mokondo: Analisis Wacana Kritis Perspektif Ilmu Komunikasi - Andhini Winariyanti; Deta Anggraini; Edison Bonartua Hutapea (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
Mass media and digital media play a strategic role in shaping public understanding of social issues, including gender relations. The phenomena of the terms pvvMass media and digital media play a strategic role in shaping public understanding of social issues, including gender relations. The phenomena of the terms pelakor (woman who steals another woman’s husband) and mokondo (slang term representing men without contribution in a relationship) have become popular discourses in Indonesian digital media. However, media representation of these two terms reveals significant gender disparities. This study aims to analyze media framing and gender bias in the representation of the pelakor and mokondo phenomena through a Critical Discourse Analysis (CDA) approach from a communication science perspective. The research method used is qualitative with Fairclough’s Critical Discourse Analysis model combined with Robert N. Entman’s framing theory. Research data consists of 4 purposively selected online news articles verified with valid URLs from major Indonesian digital media platforms (Detik.com, Kompas.com, and Tribunnews.com) in the period 2025–2026. The results show that media tends to reproduce patriarchal ideology and gender bias through unbalanced labeling and narrative construction, where women are more frequently positioned as moral subjects to be blamed in pelakor cases, while the term mokondo constructs certain stereotypes toward men in personal relationships without equivalent moral sanction. These discursive practices reinforce gender representation inequality in media. These findings offer new contributions to framing and gender studies in Indonesia by expanding the focus on the pelakor–mokondo phenomenon as a form of symbolic violence in mass communication, and underscore the urgency of gender-sensitive perspectives in journalistic practice. representation of these two terms reveals significant gender disparities. This study aims to analyze media framing and gender bias in the representation of the pelakor and mokondo phenomena through a Critical Discourse Analysis (CDA) approach from a communication science perspective. The research method used is qualitative with Fairclough’s Critical Discourse Analysis model combined with Robert N. Entman’s framing theory. Research data consists of 4 purposively selected online news articles verified with valid URLs from major Indonesian digital media platforms (Detik.com, Kompas.com, and Tribunnews.com) in the period 2025–2026. The results show that media tends to reproduce patriarchal ideology and gender bias through unbalanced labeling and narrative construction, where women are more frequently positioned as moral subjects to be blamed in pelakor cases, while the term mokondo constructs certain stereotypes toward men in personal relationships without equivalent moral sanction. These discursive practices reinforce gender representation inequality in media. These findings offer new contributions to framing and gender studies in Indonesia by expanding the focus on the pelakor–mokondo phenomenon as a form of symbolic violence in mass communication, and underscore the urgency of gender-sensitive perspectives in journalistic practice.